2022
DOI: 10.1007/s00592-021-01828-1
|View full text |Cite
|
Sign up to set email alerts
|

Early pregnancy hyperglycaemia as a significant predictor of large for gestational age neonates

Abstract: Aims We aimed to determine the effect of early pregnancy hyperglycaemia on having a large for gestational age (LGA) neonate. Methods A prospective cohort study was conducted among pregnant women in their first trimester. One-step plasma glucose (PG) evaluation procedure was performed to assess gestational diabetes mellitus (GDM) and diabetes mellitus (DM) in pregnancy as defined by the World Health Organization (WHO) criteria with International Associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…Several studies conducted worldwide have shown that a high blood glucose level is strongly associated with NAFLD 19 46 47. This may be due to alterations in lipid metabolism and inflammation within the adipose tissue and fat deposition in the liver, leading to insulin resistance 46.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…Several studies conducted worldwide have shown that a high blood glucose level is strongly associated with NAFLD 19 46 47. This may be due to alterations in lipid metabolism and inflammation within the adipose tissue and fat deposition in the liver, leading to insulin resistance 46.…”
Section: Discussion and Interpretationmentioning
confidence: 99%
“…GDM and DM were collectively labelled as HIP. The detailed protocol on baseline evaluation and glycemic status evaluation of the cohort is published elsewhere [ 33 ]. BMI of the participants were categorized according to the Asia Pacific Guidelines for BMI classification [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, over 90% of the pregnancy-related hyperglycemia occurred in low-income countries, and a quarter of all global cases are concentrated in South Asia [38]. A more recent study in Sri Lanka showed early detection of hyperglycemia in the first trimester, using the WHO diagnostic criteria, was associated with higher risk of LGA [39].…”
Section: Index Pregnancy Characteristics and Care Seekingmentioning
confidence: 99%